Marriage with the Intention of Divorce in Islamic Jurisprudence - Akhgar, Nisar Ahmad (Integrated Journal for Research in Arts and Humanities, 2024)
In Islamic law, each lawful or unlawful action is guided by underlying wisdoms and philosophies that may not be readily apparent to all. Upon deeper contemplation and analysis, the rationale behind the lawfulness or unlawfulness of actions reveals significant insights and benefits. This article addresses marriage with the intention of divorce, defined as a legitimate marriage wherein the husband, unbeknownst to the wife, intends to divorce her after a predetermined period. From the perspective of the objectives (Maqasid) of marriage, its prohibition is justified due to the lack of valid benefits within the union. However, when studied through the lens of its causes, reasons, pillars, and conditions, such a marriage, despite the husband's concealed intention for its temporary nature, meets all essential requirements without any deficiencies. This is why Islamic jurists are divided into two groups on this issue: One group, emphasizing the apparent conditions and pillars, considers it permissible, while the other, highlighting the absence of legitimate benefits, deems it prohibited. The author's preferred opinion is that it is permissible and, in cases of necessity, may be utilized. Nevertheless, the general recommendation is to discourage this practice and advise individuals to seek continuity and permanence in marriage, barring circumstances where continuation is impossible according to Islamic legal principles.